Raising a New First Amendment Hurdle for Campaign Finance “Reform” - D. Bruce La Pierre (Washington University Law Quarterly, 1998)
Proposals to regulate campaign contributions and candidates' spending invariably fly the banner of campaign finance "reform." The reformers, however, frequently have little or no evidence that particular campaign practices cause any real harm. Instead, they simply posit the existence of the disease-the corrosive effects of money on the political process-and assume that restrictions on the use of money will provide the cure. In Missouri, for example, both the legislature and the voters enacted laws in 1994 that set limits on political contributions to candidates and on candidates' campaign expenditures. These laws imposed substantial burdens on political speech and association, but they did little more than pander to public perceptions about the amorphous evils of "big money." The legislature and the voters had no evidence that contributions or expenditures in the prohibited amounts caused any identified harm, and any cure for problems in the State's elections was entirely serendipitous. The frank comment of a Missouri legislator that "[p]erception is more important than what's real" captures the substance of many measures that masquerade as campaign finance "reform." The Supreme Court, unfortunately, left the door open in Buckley v. Valeo to campaign finance reform measures, like the 1994 Missouri laws, that are grounded on little more than speculation and the cynical assumption that money necessarily and inherently corrupts the political process. Although the Buckley Court held that campaign finance measures are subject to strict scrutiny, it accepted speculation about corruption and the appearance of corruption as a justification for regulating campaign contributions. Lawyers for the American Civil Liberties Union of Eastern Missouri ("ACLU/EM") discovered a means to close the door left open in Buckley and to provide greater First Amendment protection for political speech. They persuaded the courts in the Eighth Circuit to supplement Buckley and to impose a duty on the State to demonstrate that campaign finance regulations address a "real harm." Although the Supreme Court did not review these judgments, it endorsed the Eighth Circuit's new, more demanding First Amendment standard for campaign finance laws.
Keywords: Campaign funds – Missouri; Freedom of speech; Buckley v. Valeo 424 U.S. 1 (1976)